Intratumoral blood flow in cervical cancer as assessed by transvaginal color doppler ultrasonography: Correlation with tumor characteristics. Issue 4 (1st June 2003) - Alcázar, J. L.; Castillo, G.; Jurado, M.; LÓPEZ-GARCÍA, G.
Abstract : The objective of this study was to evaluate whether intratumoral blood flow as assessed by transvaginal color Doppler ultrasonography (TVCD) correlates with some tumor features in cervical cancer. Clinical, sonographic, and histologic data on 49 women (mean age: 50.3 years, range: 25–85 years) diagnosed as having a carcinoma from the uterine cervix were reviewed. Intratumoral blood flow was assessed by TVCD in all cases. Subjective impression of the amount of flow (scanty, moderate, or abundant) as well as the lowest resistance index (RI) and highest peak systolic velocity (PSV, cm/s) were used for analysis. These data were correlated with some tumoral features such as histologic type, histologic grade, tumor volume, and tumor stage. Intratumoral blood flow was found in all cases. Abundant blood flow was found more frequently in squamous carcinoma, moderately or poorly differentiated tumors, tumors with larger volume, and advanced stage tumors ( P < 0.0001). Significantly lower RI was found in moderately or poorly differentiated tumors and advanced stage tumors ( P < 0.01) and significantly higher PSV was found in moderately or poorly differentiated tumors, tumors with larger volume, and advanced stage tumors ( P < 0.01). No correlation was found between RI and PSV and histologic type. Our data indicate that intratumoral blood flow as assessed by TVCD correlates well with some tumor features in cervical cancer.